Bowling Together? Practices of Belonging and Becoming in a London Ten-Pin Bowling League. (June 2020) - Jackson, Emma
This article uses the case of an ethnographic study of a London ten-pin bowling alley to propose a framework of 'practices of belonging and becoming' for understanding convivial participation in urban space. Drawing insights from the bowling league, the article puts forward four propositions for rethinking belonging through bowling: as a practice that embeds people in place; as a relational practice experienced across time and place; as a performance that acts on the sense of self and the body; and as a theatrical performance that enriches and resonates through a scene. The article proposes that these four intertwined registers can be used beyond this example to advance dynamic theories of belonging and to enrich an understanding of the production of convivial urban spaces in the contemporary city.